Karakteristik Fisikokimia dan Organoleptik Permen Jelly Mengkudu (Morinda citrifolia L.) dengan Variasi Penambahan Rempah - Saskia Agustin (Fakultas Teknologi Pertanian, 2026)
Noni fruit (Morinda citrifolia L.) jelly candy is a functional food product developed to increase the utilization of noni fruit, which has limited use due to its pungent aroma and sharp taste from volatile compounds such as caproic and butyric acids. The addition of spice extracts, such as ginger (Zingiber officinale Rosc.), cinnamon (Cinnamomum burmannii), and clove (Syzygium aromaticum) was aimed at masking the unpleasant sensory properties while enriching the functional value of noni jelly candy. This study determined the effect of different spice combinations on physicochemical and sensory characteristics, and identified the best formulation using an effectiveness test. This study used a Completely Randomized Design (CRD) consisting of six treatments (A1B1–A1B6) with three replications and one control. The spice combinations were formulated from ginger, cinnamon, and clove in varying volumes. Analyses included color (L*, a*, b*), texture profile (hardness, gumminess, springiness, chewiness), moisture content, ash content, total polyphenol (Folin-Ciocalteu), and antioxidant activity (DPPH). Sensory evaluation conducted color, aroma, flavor, texture, and overall acceptance. The best formulation was selected using the De Garmo effectiveness test. The results showed that spice combinations significantly affected color parameters a* and b* (p < 0.05), while L* and all texture parameters were not significantly different among treatments. Antioxidant activity and total polyphenol content differed significantly, whereas sensory parameters showed no significant differences. Treatment A1B2 (ginger 5 ml; cinnamon 10 ml; clove 5 ml) was the best formulation with an effectiveness value of 0.6502. This treatment exhibited the highest antioxidant activity (52.41%), the second highest total polyphenol content (0.005092 GAE mg/mL), favorable color and texture characteristics, and the highest sensory scores for flavor (3.96) and overall acceptance (3.80).
Validasi dan Finalisasi Ratna 4 Agustus 2026
Keywords: jelly candy; noni fruit; spice; antioxidant; physicochemical